ANALISIS SUKU BUNGA KREDIT DAN JAMINAN KREDIT TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PADA PERUSAHAAN PEMBIAYAAN DI KOTA BATAM - Christian L. Tobing, vargo; Herman, Hendri (Fakultas Ekonomi, Program Studi Akuntansi, 2020)
This research aims to look at the effect of credit interest rates and credit guarantees on credit-making decisions on financing companies in Batam. The respondents in this study were customers who borrowed from financing companies. The number of respondents in this study was 96 respondents. Data acquisition is done by disseminating questionnaires to respondents. Data that has been obtained, tabulated and analyzed using the SPSS program. From the results of the study, it was obtained that credit rates have a significant effect on credit decision-making, credit guarantees have a significant effect on credit decisions, and credit interest rates and credit guarantees simultaneously have a significant effect on credit-making decisions. The R square value in this study was 52.9% which means that the decision on credit making can be explained by the loan interest rate and credit guarantee of 52.9%, while the remaining 47.1% is explained by other variables not included in this study.